2015
DOI: 10.1080/10236244.2015.1024079
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between copper and stress indicators in the Pacific white shrimp,Litopenaeus vannamei

Abstract: Survival, clotting time, hemocyanin concentrations, total hemocyte counts, phenoloxidase activity (PO), and superoxide dismutase (SOD) of Litopenaeus vannamei juveniles (11.7 g) exposed for periods of 5, 48, and 96 h to copper (Cu) concentrations equivalent to 0.008, 1, 10, and 50% of the LC 50-96 h for L. vannamei postlarvae showed that survival was similar in all treatments, but clotting time was significantly higher with the two highest Cu concentrations. Hemocyanin had lower values after 5 h with the two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In L. vannamei exposed to metals, Bautista‐Covarrubias et al () reported a decrease in the proPO as an initial response (when exposed to Cd), but no observed in those exposed to Cu; indicating the metal‐specific response in this decapod. In the present study, the organisms exposed to sublethal metal concentrations apparently did not lose homeostasis, however when interacting with the pathogen, the indicators of immunological responses were affected.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In L. vannamei exposed to metals, Bautista‐Covarrubias et al () reported a decrease in the proPO as an initial response (when exposed to Cd), but no observed in those exposed to Cu; indicating the metal‐specific response in this decapod. In the present study, the organisms exposed to sublethal metal concentrations apparently did not lose homeostasis, however when interacting with the pathogen, the indicators of immunological responses were affected.…”
Section: Discussionmentioning
confidence: 89%
“…A significant THC reduction has been reported in WSSV‐infected shrimp (Wang et al, ). In L. vannamei juveniles exposed to Cd, Bautista‐Covarrubias et al () reported a decrease in the THC values, although this relation was not observed when exposed to Cu (Bautista‐Covarrubias et al, ). In the present study, the severe decrease of hemocyte concentrations in the WS and WS‐MM treatments during the third day of exposure might be explained by hemocyte migration as described in the case of severely infected or damaged tissues and organs (van de Braak, Botterblom, Huisman, Rombout, & van der Knaap, ; Vafopoulou, ), increasing the effect due to a possible synergistic response by exposure to metals and WSSV, because metals may affect the dynamic of disease transmission in aquaculture species (Liao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the Ni concentrations (EC 50 -96 h values) of for M. bahia and M. chulae were 24.09 and 40.61 μg L −1 , which further showed that wash water was extremely toxic. Bautista-Covarrubias et al (2015) explored the effect of Cu on pacific white shrimp, Litopenaeus vannamei . It was found that the highest mean mortality was only 8.5 ± 0.1% after 96 h of exposure to 18,650 μg L −1 of Cu.…”
Section: Discussionmentioning
confidence: 99%